Exploring the Influence of YouTube Videos on Purchase Intentions among Millennial Consumers in Tasikmalaya City - Nugraha, Ferryan (PT. Riset Press International, 2023)
The paradigm of consumer purchase decisions has been altered by the digital marketing landscape. Presently, consumers actively seek reliable and truthful information to assist them in their purchasing decisions. A noteworthy group in this regard is the Millennial generation, who dedicate a substantial amount of their time to online activities, with a particular focus on social media platforms. This generation, often referred to as